2016
DOI: 10.1115/1.4033460
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Suction and Freestream Velocity on a Hydromagnetic Stagnation-Point Flow and Heat Transport in a Newtonian Fluid Toward a Stretching Sheet

Abstract: Forced flow of an electrically conducting Newtonian fluid due to an exponentially stretching sheet is studied numerically. Free stream velocity is present and so is suction at the sheet. The governing coupled, nonlinear, partial differential equations of flow and heat transfer are converted into coupled, nonlinear, ordinary differential equations by similarity transformation and are solved numerically using shooting method, and curve fitting on the data is done by differential transform method together with Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The relevant boundary conditions at the sheet and in the free stream are given by Siddheshwar et al (2014) AND Siddheshwar and Meenakshi (2016):…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The relevant boundary conditions at the sheet and in the free stream are given by Siddheshwar et al (2014) AND Siddheshwar and Meenakshi (2016):…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…To obtain a local similarity solution for the modeled problem, the transformations are as follows (Siddheshwar and Meenakshi, 2016):…”
Section: Momentum Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the flow mechanics research for stagnation-point flow of power-law liquids taking place in the surface was studied by Pan et al (2016) and Dholey (2018). Besides, more investigations focus on stagnation-point flow under different liquids can be shown in in the following references: Mahapatra et al (2012), Pop et al (2016), Ibrahim and Makinde (2016), Siddheshwar and Meenakshi (2016), Bai et al (2019), Sivasankaran et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…fluid has some prescribed velocity. Many researchers analyzed the effect of the outer velocity and stagnation-point flow over stretching surfaces [5][6][7][8][9][10][11][12]. Mukhopadhyay and Layek [13] study the impact of variable viscosity on stretching sheet in presence of heat source/sink and reported that the thermal boundary layer increases in the presence of internal heat source.…”
Section: Introductionmentioning
confidence: 99%